Hubungan Asupan Vitamin B12 dengan Kadar Hemoglobin pada Vegetarian di Vihara Maitreya - Serlie Serlie; Gracia JMT Winaktu; Sinsanta Sinsanta; Susanty Dewi Winata (Jurnal Kedokteran Meditek, 2020)
There has been increasing interest in vegetarian lifestyle as people are more aware of the benefits of being a vegetarian. However, vegetarian diet could cause some disadvantages, one of which is vitamins deficiency. Vitamin B12 can only be found naturally in animals, thus vitamin B12 deficiency is likely to be prevalent among vegetarians. This study aimed to examine the relationship between vitamin B12 intake with haemoglobin levels in vegetarians. Seventy-four vegetarians at the Maitreya Dutamas Vihara took part in the study in February 2020. Data were collected by filling out Semi-Quantitative Food Frequency Questionnaire and having haemoglobin levels checked with Hb meter . This study is an analytical study with a cross sectional approach. The study found that most of the respondents (85.1%) did not have anaemia. The respondents (60.8%) had adequate vitamin B12 intake and most of the respondents (39.2%) did not take vitamin B12 supplementation. It can be concluded that there is no significant relationship between vitamin B12 intake and anemia (P = 0.057) in vegetarians at Dutamas Vihara.